Effect of IL-4 on the Development and Function of Memory-like CD8 T Cells in the Peripheral Lymphoid Tissues - Park, Hi-Jung; Lee, Ara; Lee, Jae-Il; Park, Seong Hoe; Ha, Sang-Jun; Jung, Kyeong Cheon (Immune network, 2016)
Unlike conventional T cells, innate CD8 T cells develop a memory-like phenotype in the thymus and immediately respond upon antigen stimulation, similar to memory T cells. The development of innate CD8 T cells in the thymus is known to require IL-4, which upregulates Eomesodermin (Eomes). These features are similar to that of virtual memory CD8 T cells and IL-4-induced memory-like CD8 T cells generated in the peripheral tissues. However, the relationship between these cell types has not been clearly documented. In the present study, IL-4-induced memory-like CD8 T cells generated in the peripheral tissues were compared with innate CD8 T cells in terms of phenotype and function. When an IL-4/anti-IL-4 antibody complex (IL-4C) was injected into C57BL/6 mice daily for 7 days, the Eomes(hi)CXCR3 (+) CD8 T cell population was markedly increased in the peripheral lymphoid organs and blood. These cells were generated from naïve CD8 T cells or accumulated via the expansion of pre-existing CD44(hi)CXCR3 (+) CD8 T cells. Initially, the majority of these CXCR3 (+) CD8 T cells expressed low levels of CD44, which was followed by the conversion to the CD44(hi) phenotype. This conversion was associated with the acquisition of enhanced effector function. After discontinuation of IL-4C treatment, Eomes expression levels gradually decreased in CXCR3 (+) CD8 T cells. Taken together, the results of this study demonstrate that IL-4-induced memory-like CD8 T cells generated in the peripheral lymphoid tissues are phenotypically and functionally similar to the innate CD8 T cells generated in the thymus.